2022
DOI: 10.3390/jcm11133621
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Changes in COVID-19 Bilateral Pneumonia Based on Optical Coherence Tomography Angiography

Abstract: The purpose of this study was to evaluate retinal and choroidal microvascular alterations with optical coherence tomography angiography (OCTA) in COVID-19 patients hospitalized because of bilateral pneumonia caused by SARS-CoV-2. The vessel density (VD) and foveal avascular zone (FAZ) of 63 patients with SARS-CoV-2 pneumonia who had positive polymerase chain reaction (PCR) tests and who recovered after receiving treatment and 45 healthy age- and gender-matched controls were evaluated and compared using OCTA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…As described in our previous paper, we excluded patients with eye and systemic diseases that could have affected the measurement outcomes, as previously described [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in our previous paper, we excluded patients with eye and systemic diseases that could have affected the measurement outcomes, as previously described [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…The foveal avascular zone (FAZ) in the SCP and in the DCP was manually delineated by two independent graders, encompassing the central fovea, where no clear and demarcated vessels were seen on the OCTA. Scan quality over 65% was a threshold for eligibility for the study, as previously described [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a new finding since there were no available studies to compare retinal volume in COVID-19-recovered patients. Some groups 18 , 20 , 23 also found that the FAZ is larger in patients who recovered from COVID-19 infection compared to normal controls; however, other groups 14 , 15 , 21 , 22 , 24 found no difference. Our group found no significant difference between the three groups regarding the FAZ area, circularity, and roundness related to COVID-19 infection or severity.…”
Section: Discussionmentioning
confidence: 92%
“…The electronic database search identified 754 articles. After screening of all titles and abstracts of potentially relevant articles, a total of 12 studies met the inclusion criteria [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ( Figure 1 ). The study characteristics and Newcastle Ottawa scores of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%